Complex coevolution of wing, tail, and vocal sounds of courting male bee hummingbirds - Clark, Christopher (2018)
Phenotypic characters with a complex physical basis may have a correspondingly complex evolutionary history. Males in the “bee” hummingbird clade court females with sound from tail-feathers, which flutter during display dives. On a phylogeny of 35 species, flutter sound frequency evolves as a gradual, continuous character on most branches. But on at least six internal branches fall two types of major, saltational changes: mode of flutter changes, or the feather that is the sound source changes, causing frequency to jump from one discrete value to another. In addition to their tail “instruments,” males also court females with sound from their syrinx and wing feathers, and may transfer or switch instruments over evolutionary time. In support of this, we found a negative phylogenetic correlation between presence of wing trills and singing. We hypothesize this transference occurs because wing trills and vocal songs serve similar functions and are thus redundant. There are also three independent origins of self-convergence of multiple signals, in which the same species produces both a vocal (sung) frequency sweep, and a highly similar nonvocal sound. Moreover, production of vocal, learned song has been lost repeatedly. Male bee hummingbirds court females with a diverse, coevolving array of acoustic traits. © 2018 The Author(s). Evolution © 2018 The Society for the Study of Evolution.